COR758, a negative allosteric modulator of GABAB receptors. (15th May 2021) - Porcu, Alessandra; Mostallino, Rafaela; Serra, Valeria; Melis, Miriam; Sogos, Valeria; Beggiato, Sarah; Ferraro, Luca; Manetti, Fabrizio; Gianibbi, Beatrice; Bettler, Bernhard; Corelli, Federico; Mugnaini, Claudia; et al.
Abstract: Allosteric modulators of G protein coupled receptors (GPCRs), including GABAB Rs (GABAB Rs), are promising therapeutic candidates. While several positive allosteric modulators (PAM) of GABAB Rs have been characterized, only recently the first negative allosteric modulator (NAM) has been described. In the present study, we report the characterization of COR758, which acts as GABAB R NAM in rat cortical membranes and CHO cells stably expressing GABAB Rs (CHO-GABAB ). COR758 failed to displace the antagonist [ 3 H]CGP54626 from the orthosteric binding site of GABAB Rs showing that it acts through an allosteric binding site. Docking studies revealed a possible new allosteric binding site for COR758 in the intrahelical pocket of the GABAB1 monomer. COR758 inhibited basal and GABAB R-stimulated O-(3-[ 35 Sthio)-triphosphate ([ 35 S]GTPγS) binding in brain membranes and blocked the enhancement of GABAB R-stimulated [ 35 S]GTPγS binding by the PAM GS39783. Bioluminescent resonance energy transfer (BRET) measurements in CHO-GABAB cells showed that COR758 inhibited G protein activation by GABA and altered GABAB R subunit rearrangements. Additionally, the compound altered GABAB R-mediated signaling such as baclofen-induced inhibition of cAMP production in transfected HEK293 cells, agonist-induced Ca 2+ mobilization as well as baclofen and the ago-PAM CGP7930 induced phosphorylation of extracellular signal-regulated kinases (ERK1/2) in CHO-GABAB cells. COR758 also prevented baclofen-induced outward currents recorded from rat dopamine neurons, substantiating its property as a NAM for GABAB Rs. Altogether, these data indicate that COR758 inhibits G protein signaling by GABAB Rs, likely by interacting with an allosteric binding-site. Therefore, COR758 might serve as a scaffold to develop additional NAMs for therapeutic intervention. Highlights: COR758 fails to displace GABAB R antagonist CGP54626 from orthosteric binding site. COR758 exerts negative allosteric effects in several functional GABAB R assays. COR758 inhibits GABAB R-stimulated O-(3-[ 35 Sthio)-triphosphate ([ 35 S]GTPγS) binding. COR758 inhibits baclofen/CGP7930-induced ERK1/2 phosphorylation in CHO-GABAB cell.